Women Empowerment in Pakistan: Multilevel Measurements, Spatial Differences, and Contributing Factors - Urooj, Komal; Ahmad, Tusawar Iftikhar; Bhatti, Muhammad Azhar; Hussain, Altaf (iRASD Journal of Economics, 2022)
Based on Pakistan Demographic and Health Survey (PDHS) 2017-18 data covering a sample of 15068 currently married females aged 15-49 years, the study intends to investigate the women empowerment situation across the regions and districts of Pakistan as well as to explore the factors affecting women empowerment in Pakistan. An index of women empowerment (ranging from score 0 to 7) was constructed by taking the sum of the seven indicators on the five dimensions: woman's participation in decision making, awareness, employment, self-esteem, and financial inclusion status. The extent of women empowerment regarding each particular indicator is gauged (in percentage) at a national level as well as at regional and district levels. Regarding each particular indicator of women's empowerment, spatial differences exist across the country at the regional and district levels. At the country level, women empowerment is poor in Pakistan. Nearly 86% of respondent women said they were currently not working (unemployed). Similarly, 92% said they did not have an account in a bank or financial institution. At the same time, 57% percent of women reported that they do not own a mobile phone, 87% indicated that they never used the internet, and 40% stated that they were not watching television. At the country level, the women empowerment index's mean score was 2.14. The mean score of the women empowerment index at the regional level stood between 0.52 (in FATA) and 3.43 (in ICT), whereas at the district level, the mean score of the index stood between 0.03 (in South Waziristan) and 4.82 (in Hunza). Out of a total of 143 districts in Pakistan, in 13 districts, the mean score of the women empowerment index remained less than 1. Findings of the ordered logit regression showed that women's higher education, age, husband's higher education, household wealth status, female headship of household, number of living children, and belongingness to the urban area are positively associated with the empowerment of women.